Streitbeilegung im Internet - Zukunft oder Irrweg? - Schüttel, Nadine (Schriften des Zentrums für Angewandte Rechtswissenschaft / ZAR, Zentrum für Angewandte Rechtswissenschaft, Karlsruher Institut für Technologie, 2014)
Alternative dispute resolution has become a focal point in politics and business. On the European level laws to support it were passed in 2013. This thesis describes the extensive background behind these developments, discusses the various methods used in theory and practice, and explores possible ways the procedure could be carried out online. At the same time, it also shows what sort of changes are necessary to smooth the path for future dispute resolution on the Internet.